2003
DOI: 10.1385/bter:93:1-3:75
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Supplementation Has No Effect on Lipoprotein Metabolism, Hemostasis, and Putative Indices of Copper Status in Healthy Men

Abstract: Pharmacological doses of zinc can adversely affect body copper status. The resulting copper deficiency can impact directly upon cholesterol metabolism and a suboptimal copper status has been observed to influence markers of hemostasis (specifically fibrinogen and the copper-containing coagulation factors V and VIII). The aim of this investigation was to examine the effect of a low level of zinc supplementation, to include dietary intake, at the United States tolerable upper intake level of 40 mg/d upon indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…22, 23 The non-significant change in HDL-C in this study was consistent with other studies. The effect of zinc supplementation in males appears to be dependent on the dose of zinc and the duration of the supplementation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…22, 23 The non-significant change in HDL-C in this study was consistent with other studies. The effect of zinc supplementation in males appears to be dependent on the dose of zinc and the duration of the supplementation.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of controlled trials which evaluated the effect of zinc supplementation on plasma lipids did not document significant changes on serum lipids with 15-150mg daily zinc. [22][23][24] On the other hand, it was shown that supplementation with 20 or 53mg zinc/day can decrease plasma cholesterol concentrations in older people with low zinc serum level.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of zinc on other monitored blood plasma indices in breeding cocks was not found in our study; the similar results were obtained by Bonham et al (2003). The presented work provides the first available experimental evidence regarding the impact of zinc supplementation on the cholesterol concentrations in blood plasma of breeding cocks.…”
Section: Discussionsupporting
confidence: 90%
“…Healthy men given 200 mg zinc/day as elemental zinc for 6 weeks showed a reduction in lymphocyte stimulation response to phytohemag glutinin as well as chemotaxis and phagocytosis of bacteria by polymorphonuclear leukocytes (Chandra et al 1984); however, no changes in lymphocyte cell number or in the proportion of lymphocyte populations were noted. Exposure of male volunteers to 0.48 mg zinc/kg/day, as zinc glycine chelate, had no effect on markers of coagulation (Bonham et al 2003b) relative to unexposed subjects. While the changes in hematological end points following long-term zinc exposure in humans are noteworthy, they were subclinical in nature, and therefore, are generally considered to be non-adverse.…”
Section: Health Effectsmentioning
confidence: 84%
“…A series of two studies (Bonham et al 2003a(Bonham et al , 2003b) evaluated a large number of hematological and immunological parameters as well as several copper-sensitive enzymes (e.g., superoxide dismutase) in healthy men exposed to 0.43 mg supplemental zinc/kg/day, and reported no significant changes resulting from zinc exposure. Studies by three other groups have evaluated exposures in the 0.6-0.8 mg zinc/kg/day range and identified slight but measurable effects.…”
Section: Oral Mrlsmentioning
confidence: 99%